Investigation of oxidant-antioxidant status in patients treated with hirudotherapy: an experimental study - Sarikan, Ismail; Savas, Hasan Basri (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the influence of hirudotherapy on parameters of oxidative stress. Method: The cross-sectional study was conducted from March 29 to September 29, 2021, at the Alanya Research and Training Hospital’s Traditional and Complementary Medicine Application Centre, Turkey, and comprised adult volunteers of either gender. The participants were subjected to two sessions of hirudotherapy 4 weeks apart. Total antioxidant status, total oxidant status, oxidative stress index values, ischemia-modified albumin level, paraoxonase 1, disulfide, native thiol, total thiol, and arylesterase levels were assessed at baseline and after the second hirudotherapy session. Data was analysed using SPSS 15. Results: Of the 50 subjects, 30(60%) were females and 20(40%) were males. The overall mean age was 47.10±15.16 years. Oxidative stress, ischemia-modified albumin and disulfide levels decreased, but not significantly (p>0.05). The reduction in disulfide levels was significant (p=0.021). Conclusion: Hirudotherapy, within its limitations, could reduce oxidative stress. Key Words: Antioxidant activity, Oxidative stress, Medicinal leeches, Hirudin.